CYTOTOXIC EFFECT OF CORCHORUS DEPRESSUS AGAINST HEPG2 AND HLE HUMAN LIVER CANCER CELLS - H Kakrani, Purvi; N Kakrani, Harish; Raval, Manan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was designed to examine the cytotoxic effects of methanolic extract of aerial parts of Corchorus depressus and hexane, chloroform, ethyl acetate, and aqueous fractions of the same extract in the human hepatocellular carcinoma (HCC) (HepG2) and invasive hepatocellular carcinoma cell lines (HLE). Methods: Anti-proliferative effects were evaluated using 3-(4,5-dimethythiazol2-yl)-2,5-diphenyl tetrazolium bromide (MTT) and neutral red uptake (NRU) assay. Human HCC (HepG2) and invasive hepatocellular carcinoma cell lines (HLE) were treated with different concentrations of methanolic extract (10, 25, 50, 100, 200, 300, 400, and 500 Î¼g/mL) of aerial parts of C. depressus as well as hexane, chloroform, ethyl acetate, and aqueous fractions (200 Î¼g/mL) for 24 and 48 h. The cell viability and the half maximal inhibitory concentration (IC50) were determined. Results: The maximum cytotoxic effect was noticed with a maximum dose of methanolic extract (500 Î¼g/mL) and alkaloidal fraction (200 Î¼g) in this study with an IC50 value of about 200 Î¼g. Conclusion: The set of studies showed that methanolic extract of aerial parts of C. depressus and alkaloidal, chloroform and ethyl acetate fractions fractions was capable of inhibiting cell growth and cell proliferation by inducing cytotoxicity of HepG2 and HLE cells.